"To Me, There's Always a Bias": Understanding the Public's Folk Theories About Journalism. (26th October 2021) - Wilner, Tamar; Montiel Valle, Dominique A.; Masullo, Gina M.
ABSTRACT: This study investigates how Americans conceive of journalistic processes and how their conceptions clash with the way journalists construct their profession. We do this by interpreting data from five focus groups to explore ways the public understands journalism, through what are called folk theories. We find that participants broadly interpreted what makes a story biased – seeing common journalistic practices, such as adding context to a story, as avenues of bias. We also found that the public's understanding of common journalistic practices, such as eyewitness interviews and investigative work, is compatible with the journalistic self-conception, but the public may attribute negative intent if they see a story that lacks these characteristics. The data show participants hold high expectations for journalism that journalists may view as unattainable.